Pengaruh Lama Pengeringan Terhadap Karakteristik Organoleptik Teh Herbal Kulit Pala (Myristica fragrans Houtt.) - Palijama, Syane (Politeknik Negeri Ketapang, 2024)
The aim of this research was to determine the appropriate drying time for the organoleptic characteristics of nutmeg peels herbal tea. This research used a completely randomized design with 4 levels of drying time treatment, namely: T1 = 3 hours, T2 = 6 hours, T3 = 9 hours, T4 = 12 hours, and repeated 3 times. The results of the research showed that the 12 hour drying treatment with organoleptic characteristics, both hedonic test and hedonic quality test, respectively, included: color with a scale value of 4.45 (like) and 4.19 (brownish yellow), taste with a scale value of 4.49 ( like) and 4.82 (very nutmeg-tasted) and overall acceptance of 4.68 (very like). The drying time of 3 hours has an effect on the flavour of nutmeg peels herbal tea with an assessment score of 4.08 (like it) and 4.67 (very nutmeg-flavored).